Antibiogram Pattern Of Bacterial Isolates From Subclinical Mastitis In Cows - Langer, Anil; Nauriyal , D.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
From 69 lactating cows of University livestock farm , a total of 266 quarters were screened for subclinical mastitis (SCM), 89 quarters were found to be positive which resulted in the recovery of 190 bacterial isolates. Of these, 50 (56.17%) quarters yielded monomicrobic isolates whereas 39 (43.82%) quarters harboured mixed infection. On bacteriological culture examination, a total of 190 bacterial isolates were recovered which comprised of 54 isolates of CPS, 115 isolates of CNS 2 isolates of Micrococcous varians, 11 isolates of Str. agalactiae and 8 isolates of coliforms.In the present study a total of 67 isolates comprising of 57 gram positive and 10 gram-negative isolates were studied for their antibiogram pattern against 20 antibacterial drugs . Results of in vitro drug susceptibility testing on gram-positive and gram-negative bacterial isolates showed that most of the broad-spectrum antibacterial drugs were found highly effective against isolates recovered from cases of subclinical mastitis. The sensitivity profile of isolates showed poor sensitivity towards commonly used antibacterial drugs penicillin, ampicillin and amoxyclav.